Casein kinase 1γ acts as a molecular switch for cell polarization through phosphorylation of the polarity factor Tea1 in fission yeast. (2nd November 2015) - Koyano, Takayuki; Barnouin, Karin; Snijders, Ambrosius P.; Kume, Kazunori; Hirata, Dai; Toda, Takashi
Abstract : Fission yeast undergoes growth polarity transition from monopolar to bipolar during G2 phase, designated NETO (New End Take Off). It is known that NETO onset involves two prerequisites, the completion of DNA replication and attainment of a certain cell size. However, the molecular mechanism remains unexplored. Here, we show that casein kinase 1γ, Cki3 is a critical determinant of NETO onset. Not only did cki3 ∆ cells undergo NETO during G1‐ or S‐phase, but they also displayed premature NETO under unperturbed conditions with a smaller cell size, leading to cell integrity defects. Cki3 interacted with the polarity factor Tea1, of which phosphorylation was dependent on Cki3 kinase activity. GFP nanotrap of Tea1 by Cki3 led to Tea1 hyperphosphorylation with monopolar growth, whereas the same entrapment by kinase‐dead Cki3 resulted in converse bipolar growth. Intriguingly, the Tea1 interactor Tea4 was dissociated from Tea1 by Cki3 entrapment. Mass spectrometry identified four phosphoserine residues within Tea1 that were hypophosphorylated in cki3 ∆ cells. Phosphomimetic Tea1 mutants showed compromised binding to Tea4 and NETO defects, indicating that these serine residues are critical for protein–protein interaction and NETO onset. Our findings provide significant insight into the mechanism by which cell polarization is regulated in a spatiotemporal manner. Abstract : When Tea1 is entrapped by Cki3 to the cell membrane, Tea1 is hyperphosphorylated, thereby becoming inactive for the potentiation of growth from the cell tip. Under this condition, interaction between Tea1 and Tea4 is compromised. Phosphomimetic Tea1 recapitulates the nongrowth phenotype.